DESAIN KURIKULUM BERBASIS KOMPETENSI KKNI PADA PRODI TEKNIK - Ishak Ishak (Rang Teknik Journal, 2020)
Abstract: The existing learning today, more inclined to competitive learning that emphasizes more on the cognitive aspects only so that students get a great course value but has a high individualistic nature, smart only for himself without wanting to share teaching his knowledge with other friends. This paradigm must be changed, into contextual and collaborative learning. The research method used in this study is the method of literature study and secondary data collection. The results of this study are that the KKNI competency-based curriculum, is a curriculum design that is very relevant to be applied in tertiary institutions especially at the level of study programs in order to prepare superior and competitive human resources in the world of work. There are three categories of curriculum designs in civil engineering study programs: (1) subject centered design; (2) student centered design ; (3) the problem centered designs.